Tsunami data assimilation of Cascadia seafloor pressure gauge records from the 2012 Haida Gwaii earthquake. Issue 9 (2nd May 2016) - Gusman, Aditya Riadi; Sheehan, Anne F.; Satake, Kenji; Heidarzadeh, Mohammad; Mulia, Iyan Eka; Maeda, Takuto
Abstract: We use tsunami waveforms recorded on a dense array of seafloor pressure gauges offshore Oregon and California from the 2012 Haida Gwaii, Canada, earthquake to simulate the performance of two different real‐time tsunami‐forecasting methods. In the first method, the tsunami source is first estimated by inversion of recorded tsunami waveforms. In the second method, the array data are assimilated to reproduce tsunami wavefields. These estimates can be used for forecasting tsunami on the coast. The dense seafloor array provides critical data for both methods to produce timeliness (>30 min lead time) and accuracy in both timing and amplitude (>94% confidence) tsunami forecasts. Real‐time tsunami data on dense arrays and data assimilation can be tested as a possible new generation tsunami warning system. Key Points: First demonstration of tsunami data assimilation method using seafloor pressure gauge array records Inverted tsunami source for the 2012 Haida Gwaii earthquake consists of large fault slip and bathymetric slope displacement effect Assimilation of dense tsunami data yields forecast similar to forward simulation from the source model